Ketepatan Menjelaskan Sistem Kurikulum pada Proses Pembelajaran di SDN Sumbertlaseh 2 Desa Sumbertlaseh - Af Idatun Nisa’; Sri Minarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The curriculum is one of the important elements in education which functions as a guide for carrying out learning activities at school. The success of education really depends on the teacher's ability to understand and describe the existing curriculum system. This research aims to reveal the importance of teacher accuracy in describing the curriculum system during the learning process at SDN Sumbertlaseh 2 Sumbertlaseh Village. The method applied in this research is a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The results of the research show that teachers' accuracy in understanding and explaining the curriculum system can help the learning process take place more efficiently, increase students' understanding of the material being taught, and support the achievement of educational goals more optimally. Therefore, teachers need to improve their understanding of the structure and implementation of the curriculum so that the learning process becomes better.